Professionals' Identification Within and Across Science, Technology, Engineering, and Mathematics (STEM) Fields. (December 2021) - Simpson, Amber; Collazo, Jose Morales; Zilvinskis, John; Maltese, Adam
Professional identity, for many, is a substantial component of their career choices and development. In this study, we utilized data from an online survey completed by 1, 867 participants living across the United States to consider the extent to which an individual working in science, technology, engineering, and/or mathematics (STEM) field identifies with each discipline, and how this may be associated with recognition, competence, and sense of belonging. Results from structural equation modeling indicated that participants' STEM field had a positive, direct impact on their discipline-specific identity but a negative, direct impact on other discipline identities. Furthermore, recognition and competence had significant direct and indirect effects on participants' STEM identity, which was not consistent by STEM field. Alternatively, sense of belonging and self-identifying as a woman had limited effects in our model. Our findings raise questions as to the possibility (or not) of STEM as an interdisciplinary identity for professionals with a career in STEM.